Investigation of sol-gel derived BaCl2:Eu2+ luminescent nanophosphor and the corresponding PVP@BaCl2:Eu2+ polymer nanocomposite. (10th July 2018) - Secu, C E; Negrila, C; Secu, M
Abstract: We have prepared Eu 2+ (1%) doped BaCl2 nanopowders by using a hybrid sol-gel/thermal decomposition route using barium acetate and trichloracetic acid as in situ chlorination agent. Structural and thermal analysis data have shown that orthorhombic BaCl2 phase crystallization occurs at 260 °C. BaCl2 :Eu 2+ nanocrystals of about 100–200 nm in size were produced after annealing (in air) at 500 °C and they displayed Eu 2+ d → f type luminescence at 396 nm. X-ray photoelectron spectroscopy indicated the presence of both Eu 2+, Eu 3+ ions species and a BaO passivating layer at the surface of the nanocrystals. A polymer nanocomposite (PVP@BaCl2 :Eu 2+ ) was also processed and its optical response under x-ray irradiation was found to be similar to that of the nanopowder. X-ray excited luminescence showed Eu 2+ luminescence at 396 nm, whereas the thermoluminescence peak at 130 °C was assigned to the F(Cl)-center recombination with Eu 2+ related hole centers.